Applying the ESC 2016, H2FPEF, and HFA‐PEFF diagnostic algorithms for heart failure with preserved ejection fraction to the general population. (29th August 2021) - Nikorowitsch, Julius; Bei der Kellen, Ramona; Kirchhof, Paulus; Magnussen, Christina; Jagodzinski, Annika; Schnabel, Renate B.; Blankenberg, Stefan; Wenzel, Jan‐Per
Abstract: Aims: Heart failure with preserved ejection fraction (HFpEF) is common in patients presenting with dyspnoea. Recently, clinical tools were developed to facilitate the diagnosis of HFpEF. Here, we apply the European Society of Cardiology (ESC) 2016 heart failure guidelines and the H2 FPEF and HFA‐PEFF scores to a middle‐aged sample of the general population and compared the different groups with each other. Methods and results: This study included the first 10 000 participants of the population‐based Hamburg City Health Study. A total of 5613 subjects, aged 62 ± 8.7 years (51.1% women), qualified for the analysis. Unexplained dyspnoea was present in 407 (7.3%) subjects. In those, the estimated prevalence of HFpEF was 20.4% (ESC 2016), 12.3% (H2 FPEF), and 7.6% (HFA‐PEFF). The majority of subjects was classified as HFpEF not excludable according to the HFA‐PEFF (57.7%) and H2 FPEF (59.2%) scores. For all algorithms, subjects diagnosed with HFpEF showed elevated age and body mass index as well as a higher prevalence of atrial fibrillation, diabetes, and arterial hypertension compared with those without HFpEF or HFpEF not excludable. The distribution of those co‐morbidities and risk factors varied between the differently diagnosed HFpEF groups with the highest burden in the HFpEF group defined by the H2 FPEF score. The overlap of subjects diagnosed with HFpEF according to the different algorithms was very limited. Conclusions: Unexplained dyspnoea is common in the middle‐aged general population. The ESC 2016 algorithm and the H2 FPEF and HFA‐PEFF scores detect different, discordant subpopulations of probands with breathlessness. Further classification of the HFpEF syndrome is desirable.